Willingness of farmers to pay for satellite-based irrigation advisory services: a southern Italy experience. (22nd August 2018) - Altobelli, F.; Lall, U.; Dalla Marta, A.; Caracciolo, F.; Cicia, G.; D'Urso, G.; Del Giudice, T.
Abstract: The aim of the current study was to define, optimize and customize IRRISAT, a fully operative satellite-based irrigation advisory service (IAS) provided in Campania Region, Italy, using a choice experiment to determine the preferences of farmers regarding the main characteristics and attributes of IRRISAT. Furthermore, willingness to pay for the main attributes of the services provided was estimated. The information on the amount of water required for irrigation provided by the IAS is sent out to farmers via SMS and email, as well as via the IRRISAT webpage. The study was related to the 2013–2014 irrigation season, when the service provided support to 669 farmers over an area of 55 ha. The study considered four attributes and levels of IRRISAT service: land management unit (scale of service); different levels of water saving (5, 10 and 30%) that could be achieved at different prices; annual fee paid by farmers (ranging between €6 and €10/ha/year); length of contract for the service supply, ranging from 1 to 3 years. Results showed that farmers' preferences are influenced positively by scale (entire area of the farm instead of single fields) and duration of the service delivering contract. Concerning the duration of the contract, the most preferred option was the 3-year service. Finally, water saving was shown to affect farmers' choices very little and thus it is probably less attractive for farmers probably due to the low price and to a relatively large availability of water for irrigation.